Insights into the Trenchward Displacement of the Volcanic Activity in the Colima Volcanic Complex, Mexico - Alvarez , Román; Yutsis , Vsevolod (Emerging Issues in Environment, Geography and Earth Science Vol. 1, 2023)
This chapter presents gravimetric and aeromagnetic data in the region of the CVC, as well as the associated anomaly maps, several 2-D models along selected cross-sections, and two inversions, one gravimetric and the other magnetic, of such fields. Geological mapping of areas with potential for volcanic hazards is of high priority. In Mexico, volcanic cartography is in an early stage of development. Volcanological research has been mostly limited to pyroclastic and geochemical studies, with very little attention paid to detailed mapping of active volcanoes. Ancestral Volcán Colima grew on the southern, trenchward flank of the earlier and larger volcano Nevado de Colima. Trenchward collapse was favored by the buttressing effect of Nevado, the rapid elevation drop to the south, and the intrusion of magma into the southern flank of the ancestral volcano. Modeling gravimetric and aeromagnetic data we locate the magma chambers of the Fuego (active) and Nevado (extinct) volcanoes within a 65 mGal negative Bouguer anomaly elongated in a nearly N-S direction. A magnetic high is visible over the southern part of the Fuego volcanic edifice on the accompanying aeromagnetic map. Two further, related formations that we discovered appear to follow the southerly magmatic migration trend and whose abnormalities have not been previously reported. One of them is a collapse structure with a circular topographic expression, and the southernmost is a low-density intrusion ~1 km below sea level, associated with a moderate topographic bulge at the surface that we interpret as a magma body. Gravimetric and magnetic fields are concurrently modeled along five lines that cross the anomalies in order to identify the magmatic bodies. We also perform 3-D gravimetric and magnetic inversions in addition to the 2-D models. Although they are unable to differentiate between the separate chambers of the Nevado and Fuego volcanoes, the results of each inversion sufficiently and independently identify the location of the magmatic chambers. 2-D and 3-D results complement each other and consistently show the locations of potential magmatic regions. The southern borders of the CVC can now be included in the observation on the southward-younging activity. The alignment of the Nevado volcano, Fuego volcano, La Escondida structure, and Southern Magma Chamber suggests that volcanism's southward migration is a dynamic, continuous activity, and their proximity and order favor a shared origin for them. Our models support a multiple, complex magmatic system that appears to continue to spread southwardly, which can pose additional volcanic risks to an already threatened local population.